Panax notoginseng saponins attenuate lung cancer growth in part through modulating the level of Met/miR-222 axis. (4th December 2016) - Yang, Qinbo; Wang, Peiwei; Cui, Jingang; Wang, Wenjian; Chen, Yu.; Zhang, Teng
Abstract: Ethnopharmacological relevance: Panax notoginseng saponins (PNS) are the major chemical constituents of Panax notoginseng (Burkill) F.H. Chen (Araliaceae), a medicinal herb extensively used in China for the treatment of various diseases including cancer. PNS have been reported to contribute to the therapeutic effects of Panax notoginseng in disease conditions including lung cancer. Aim of the study: The current study aims to further understand the molecular mechanisms implicated in the pharmacological activities of PNS in attenuating lung cancer growth. Materials and methods: Lewis lung carcinoma (LLC) cell line was employed and the impact of PNS treatment on the viability of LLC cells was first examined in vitro . The tumor-suppressive effect of PNS was further validated in vivo by assessing the tumor growth in BALB/c mice inoculated with LLC cells. Whole genome microarray and real-time PCR analyses were performed to examine and verify altered expression of genes associated with PNS treatment. Real-time PCR and western blotting analyses were also carried out to investigate the implication of microRNA (miRNA)-mediated gene expression regulation in the anti-tumor activity of PNS. Results: PNS treatment resulted in selective impairment of the survival of LLC cells. Furthermore, PNS treatment led to attenuated growth of tumors derived from inoculated LLC cells in mice. Bioinformatic analyses of gene expression profiles revealed that multiple pathways associated with tumorigenesis were significantly modulated by PNS treatment in vivo . The expression of an array of genes promoting tumorigenesis and progression including Hgf, Met, Notch3, Scd1, Epas1, Col1a1, Raf1, Braf1 and CDK6 was significantly decreased by PNS treatment, whereas the expression of tumor suppressive Rxrg was significantly increased as a result of PNS treatment. The level of miR-222, a miRNA regulated by Met, was significantly decreased by PNS treatment. The expression of tumor suppressor p27 and PTEN, miR-222 target genes, was significantly increased by PNS treatment. Conclusion: Out work here presented novel evidence demonstrating that multiple mechanisms were implicated in the anti-tumor effects of PNS in lung cancer models. Particularly, PNS treatment significantly modulated the level of Met/miR-222 axis in LLC cells. Increased understanding of the anti-tumor mechanisms of PNS may provide further experimental evidence to help optimize the therapeutic modalities for the treatment of lung cancer and other types of cancer. Graphical abstract: